2015
DOI: 10.1186/s12866-015-0414-8
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic characterization of Bacillus anthracis in Guizhou Province, Southwest of China

Abstract: BackgroundBacillus (B.) anthracis is the pathogen that causes fatal anthrax. Guizhou Province is an old foci of anthrax in the southwest of China. Human anthrax has also been frequently reported in Guizhou in recent year. However, there is limited information on the genetic background of local B. anthracis isolates in Guizhou Province. Strain-specific detection of this bacterium using molecular approaches has enhanced our knowledge of microbial genetics. In the present study, we employed Multiple Locus Variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Some farming regions in China are in naturally infectious areas prone to anthrax outbreaks; livestock are commonly infected by B. anthracis during farming, so many recurrent animal anthrax cases are reported (17). Guizhou Province is a historical center of anthrax in China, and sporadic human anthrax epidemics have happened frequently in Guizhou Province in recent years (9,10,18,19). In this study, a case of suspected anthrax case was reported to the Guizhou Provincial CDC in September 2016.…”
Section: Discussionmentioning
confidence: 68%
“…Some farming regions in China are in naturally infectious areas prone to anthrax outbreaks; livestock are commonly infected by B. anthracis during farming, so many recurrent animal anthrax cases are reported (17). Guizhou Province is a historical center of anthrax in China, and sporadic human anthrax epidemics have happened frequently in Guizhou Province in recent years (9,10,18,19). In this study, a case of suspected anthrax case was reported to the Guizhou Provincial CDC in September 2016.…”
Section: Discussionmentioning
confidence: 68%
“…Cutaneous anthrax is a zoonotic infection caused by the bacteria Bacillus anthracis, which is responsible for over 95% of all anthrax cases [11]. In China, the growth of the livestock industry and the rise in cattle and sheep farming have led to an increase in localized outbreaks of cutaneous anthrax, causing panic among people and imposing a signi cant burden on socioeconomic development [20][21][22][23]. Thus, the characteristics of concentrated cutaneous anthrax cases in endemic regions need to be analyzed, and effective treatment strategies need to be investigated for the diagnosis and management of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…The main pathogenic bacteria in the genus Brucella are Brucella suis, B. melitensis and B. abortus. The brucellosis epidemic is mainly caused by B. melitensis in Guizhou Province [35]. Brucellosis has covered nine cities or states in Guiyang, Qiannan, Qiandongnan, Tongren, Zunyi, Qiannan, Liupanshui, Anshun, and Bijie as well as Gui'an New District [36], and the prevention and control situation is grim.…”
Section: Discussionmentioning
confidence: 99%